Are bank risk disclosures informative? Evidence from debt markets - Mohamed Elmagrhi (International Journal of Finance & Economics, 2021)
This study examines whether financial reporting with a specific focus on risk disclosures have a predictive (informative) effect on banks’ credit ratings (BCRs) and, consequently, ascertains whether governance structures can moderate such an association. Using one of the largest bank-level datasets collected from 12 Middle East and North African (MENA) countries over the 2006-2013 period to-date, our findings are as follows. First, we find that risk disclosures have a predictive effect on BCRs. Second, we find that the relationship between risk disclosures and BCRs is contingent on the quality of governance structures. Specifically, we find that the informativeness of risk disclosures on BCRs is higher in banks with larger board size, greater independence, higher government ownership, and better Shariah supervisory board, but lower in banks with greater block ownership, higher foreign ownership and the presence of CEO duality. The central tenor of our findings remains unchanged after controlling for a number of firm- and country-level factors, alternative risk disclosure measures, firm- and national-level governance proxies, different types of banks, and potential endogeneities. The findings have important implications for investors, especially bondholders, standard-setters, regulators, and central governments.